2022
DOI: 10.1101/2022.11.24.517859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

retro-Tango enables versatile retrograde circuit tracing inDrosophila

Abstract: Transsynaptic tracing methods are crucial tools in studying neural circuits. Although a couple of anterograde tracing methods and a targeted retrograde tool have been developed inDrosophila melanogaster, there is still need for an unbiased, user-friendly, and flexible retrograde tracing system. Here we describeretro-Tango, a method for transsynaptic, retrograde circuit tracing and manipulation inDrosophila. In this genetically encoded system, a ligand-receptor interaction at the synapse triggers an intracellul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…With the split-GAL4 approach we identified five distinct neuronal sub-types that can induce PMRs. To find out whether these neurons receive input from distinct entry points in the brain and to identify the target neurons of these mSP responsive neurons, we used the retro- and trans -Tango technique to specifically activate reporter gene expression in up- and down-stream neurons (Sorkaç et al, 2023; Talay et al, 2017) (Figures 7A-O).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the split-GAL4 approach we identified five distinct neuronal sub-types that can induce PMRs. To find out whether these neurons receive input from distinct entry points in the brain and to identify the target neurons of these mSP responsive neurons, we used the retro- and trans -Tango technique to specifically activate reporter gene expression in up- and down-stream neurons (Sorkaç et al, 2023; Talay et al, 2017) (Figures 7A-O).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous results that the SP response can be induced via multiple pathways (Haussmann et al, 2013) , we found distinct sets of neurons in the central brain and the abdominal ganglion that can induce PMRs via expression of mSP. Mapping the pre- and post-synaptic connections of the distinct SP target neurons by retro- and trans -Tango (Sorkaç et al, 2023; Talay et al, 2017) revealed that SP target neurons direct higher order sensory processing in the central brain. These neurons feed into two common post-synaptic neuronal subtypes indicating that SP interferes with the integration of diverse sensory inputs to build a stereotyped output either reducing receptivity and/or increasing egg laying.…”
Section: Introductionmentioning
confidence: 99%
“…We identified a total of 84 presynaptic partners using BrainCircuits with a complex distribution over the brain (Figure 6D), though most of the connectivity was found within the SEZ. Additionally, we used retro-Tango 54 , a retrograde transsynaptic technique that employs similar trans-synaptic mechanisms as trans-Tango but in the retrograde direction. This experiment showed that SELK neurons receive most of the presynaptic input from neurons located in the SEZ (Figure 6E), consistent with the data derived from the FAFB analysis.…”
Section: Connectivity Of Selk Neurons Within the Drosophila Brainmentioning
confidence: 99%
“…The BAcTrace approach restricted the connectivity analysis to uPNs. We therefore used another pan-neuronal retrograde tracer, retro-Tango 37 to label all the presynaptic partners of PD2a1/b1 (Fig. 5i).…”
Section: Main Textmentioning
confidence: 99%